﻿﻿Effects of Increasing Dietary Standardized Ileal Digestible Lysine on 15 to 24 lb Nursery Pigs - A. B. Clark; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; R. D. Goodband; J. C. Woodworth; K. Touchette (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 300 nursery pigs (PIC 327 × 1050, initially 14.8 lb BW) were used in a 28-d growth trial to evaluate the effects of increasing dietary standardized ileal digestible (SID) lysine (Lys) on nursery pig growth performance. Pigs were weaned at approximately 21 d of age and allotted to the pens according to BW and gender. A common starter diet was fed for 6 d, then pens were allotted to 1 of 6 dietary treatments in a completely randomized design. Experimental diets were fed for 14 d followed by a common diet for 14 d. The 6 dietary treatments were formulated to contain 1.10, 1.20, 1.30, 1.40, 1.50, and 1.60% SID Lys. Increasing SID Lys resulted in improved (linear, P<0.001) ADG and F/G during d 0 to 14 when experimental diets where fed, with no differences observed in ADFI. For ADG, broken line linear (BLL) and quadratic polynomial (QP) models demonstrated similar fits, with maximum ADG at 1.45% and above 1.60% for BLL and QP models, respectively. Similar estimates were found when modeling feed efficiency. In conclusion, this experiment determined that the SID Lys requirement for 15 to 24 lb nursery pigs was at least 1.45% SID Lys for both ADG and feed efficiency.
Keywords: lysine; growth; nursery pigs; swine